Polyprenylated Acylphloroglucinols With Different Carbon Skeletons From the Fruits of Garcinia multiflora - Teng, Haida; Li, Qingqing; Ma, Ziyu; Li, Xueni; Xie, Wenli; Chen, Yu; Yang, Guangzhong (Frontiers in Chemistry, 2021)
Eleven new polycyclic polyprenylated acylphloroglucinols (PPAPs, 1–11) and three new monocyclic polyprenylated acylphloroglucinols (MPAPs, 12–14), together with ten known analogues were isolated from the fruits of Garcinia multiflora. These PPAPs belong to three types including the bicyclic polyprenylated acylphloroglucinols (BPAPs), the caged PPAPs, and the complicated PPAPs. Their structures and absolute configurations were determined through HRESIMS, NMR spectroscopy data, electronic circular dichroism (ECD) calculations, and gauge-independent atomic orbital (GIAO) NMR calculations with DP4+ analyses. Moreover, compounds 2 and 7 exhibited moderate cytotoxicity against three human cancer lines (MCF-7, T98, and HepG2) with IC50 values ranging from 9.81 ± 1.56 to 17.00 ± 2.75 μM.